2014
DOI: 10.1371/journal.pone.0090782
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Thermal Infrared Imaging in Human Stress Research

Abstract: High resolution thermal infrared imaging is a pioneering method giving indices of sympathetic activity via the contact-free recording of facial tissues (thermal imprints). Compared to established stress markers, the great advantage of this method is its non-invasiveness. The goal of our study was to pilot the use of thermal infrared imaging in the classical setting of human stress research. Thermal imprints were compared to established stress markers (heart rate, heart rate variability, finger temperature, alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
154
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(168 citation statements)
references
References 49 publications
13
154
1
Order By: Relevance
“…In hens there is a significant drop in comb surface temperature in response to anticipation and consumption of a palatable food reward [36] but also during exposure to unpleasant events [73]. This contrasting effect on body temperature can be explained in terms of activation of the sympathetic branch of the ANS which induces an increase in core temperature, reflected in the eye, and a decrease in more peripheral body area, such as nose, face and ears, due to vasoconstriction [49,50,74,75].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In hens there is a significant drop in comb surface temperature in response to anticipation and consumption of a palatable food reward [36] but also during exposure to unpleasant events [73]. This contrasting effect on body temperature can be explained in terms of activation of the sympathetic branch of the ANS which induces an increase in core temperature, reflected in the eye, and a decrease in more peripheral body area, such as nose, face and ears, due to vasoconstriction [49,50,74,75].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…With advancements in commercial thermal imaging technologies, thermography has begun to extend its application context to the analysis of people's physiological processes and affective states. Indeed, it has been shown that physiological signatures, such as thermal directional changes (e.g., [4], [12]- [14]), cardiac (e.g., [11]), perspiratory (e.g., [15]) and respiratory (e.g., [8]) indices, and muscular activations related to facial expressions (e.g. FACS decoding [20]), can be captured through thermal imaging.…”
Section: Literature Review: a Short Summarymentioning
confidence: 99%
“…FACS decoding [20]), can be captured through thermal imaging. Researchers have investigated thermal signatures of one's face in relation to mental stress, (e.g., [4], [13], [21]- [23]). For example, it was found that a person's nose tip could show temperature drops under cognitive load inducing mental stress [4].…”
Section: Literature Review: a Short Summarymentioning
confidence: 99%
See 2 more Smart Citations